Empowering community health volunteer on community-based tuberculosis case management programs in lower-income countries: A systematic review - Muhamad Jauhar; I Gusti Ayu Putu Desy Rohana; Utami Rachmawati; Lita Heni Kusumawardani; Rasdiyanah Rasdiyanah (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2019)
Globally, almost 40% of tuberculosis clients are undiagnosed and delayed treatment. This condition leads to disease transmission and increasing new cases. Healthcare workers and community health volunteers as an active case finding frontliner and case manager in the community. The elevated numbers of new case findings and comprehensive management of diseases are the successful indicators of the tuberculosis prevention program. This study identified research articles related to community health volunteer empowerment in tuberculosis case management. Literature study of 20 articles from journal database, such as: Science Direct, Proquest, Scopus, and EBSCO for the last 5 years. It used keywords tuberculosis, community volunteer or empowerment, community-based early case finding. Data were analyzed in tables consist of title, author, year, methodology, result, and recommendation. The empowerment of the community health volunteers was effective in increasing tuberculosis case finding, especially in the border areas, remote areas and rural area. The existence of the community health volunteers brought tuberculosis services closer to the community and able to minimize barriers of health access and costs. Increasing the capacity of the community health volunteers is needed to support their role. Community health volunteers with a history of tuberculosis or from a family with tuberculosis are more acceptable in the community so the success of case finding and treatment is achieved. Community health volunteers worked through home visits were able to change community’s perspectives, promote the formation of health seeking behavior and minimize public-stigma. The empowerment of the community health volunteers is essentially needed as the alternative strategies to find new cases in the community and strengthen its management. There need to provide a wholesome moral and material support from the government for the community health volunteers. This can be integrated into the management of tuberculosis programs in primary health care facilities.